More than Eco-efficiency is Required to Improve Food Security - Park, S.E.; Howden, S.M.; Crimp, S.J.; Gaydon, D.S.; Attwood, S.J.; Kokic, P.N. (Wiley, 2010)
Agricultural eco‐efficiency is promoted as a means of increasing agricultural production and improving the security of food systems in response to climate change. The rationale is that economic and environmental resources will be used more efficiently, enabling increased amounts of food to be produced from the same amount or fewer inputs. We used (i) a quantitative literature analysis to examine current usage of the eco‐efficiency concept to assess strategies aimed at improving food security under climate change, and (ii) a wheat (Triticum aestivum L.) simulation experiment to consider possible tradeoffs between economic benefits of agricultural intensification, environmental performance, and social impacts. Two issues were highlighted from this. First, the relationship between economic and environmental outcomes is regularly assumed, leading to potentially erroneous conclusions and unintended outcomes. Second, the lack of any consideration for the social dimensions of food security ignores variability in incomes generated from agricultural production, and the potential for reduced quantities of food to be produced as a rational response to maximizing gross margins. We suggest the eco‐efficiency concept explicitly include social as well as economic and environmental criteria if it is to avoid poor rates of uptake of eco‐efficiency technologies, the promotion of practices that reduce the effectiveness of hunger‐reduction efforts, and unintended environmental degradation.